Pengaruh Model Pembelajaran Berbasis Masalah berbantuan Chatbot AI terhadap Higher Order Thinking Skill - Setyo Aji Wibowo; Intan Faizah (STAB Kertarajasa, 2023)
This study aims to determine the effect of problem-based learning models assisted by AI chatbots on higher-order thinking skills in Class IV at SDN 1 Genteng Kec. Genteng, Kab. Banyuwangi, East Java. This type of research uses a quantitative approach with a quasi-experimental research method and a Non-equivalent Control Group Design. Non-probability sampling was used. The population and sample consisted of 33 students in class IV-A as the experimental class and 39 students in class IV-B as the control class in SDN 1 Genteng, Kec. Genteng, Kab. Banyuwangi, East Java. The data-collection instrument used a written test in the form of multiple choices and descriptions. Data analysis techniques using SPSS Statistics 21. The results of the study showed that problem-based learning models assisted by AI chatbots affected learning outcomes. Other results using problem-based learning models assisted by chatbot AI are different from those obtained using conventional models. The improved learning outcomes based on the N-Gain score of problem-based learning models assisted by AI chatbots is 56.1545, and that of conventional models is 21.0266. It can be concluded that the use of problem-based learning models assisted by AI chatbots is effective in elementary school learning.